Thermally-induced neuronal plasticity that mediates heat tolerance [data] - Ambroziak, Wojciech; Nencini, Sara; Pohle, Jörg; Žuža, Kristina; Pino, Gabriela; Lundh, Sofia; Araujo Sousa, Carolina; Götz, Larissa; Schrenk-Siemens, Katrin; Manoj, Gokul; Gutierrez-Herrera, Mildred A.; Acuna Goycolea, Claudio; et al. (Universität, 2024)
Heat acclimation is an adaptive process that improves physiological performance and supports survival in the face of increasing environmental temperatures. Understanding the underlying mechanisms holds potential to mitigate health risks and reduce the steadily increasing number of heat-related casualties associated with global warming. Here we report the identification of a discrete group of hypothalamic preoptic neurons that transform to rheostatically increase their activity over the course of heat acclimation, a property required for mice to become heat tolerant. Peripheral thermo-afferent pathways via the Parabrachial Nucleus activate preoptic neurons and mediate acute heat-defense mechanisms in non-acclimated animals. However, long-term heat exposure promotes the preoptic neurons to gain intrinsically warm-sensitive activity, independent of thermo-afferent parabrachial input. Our data shows that their newly gained cell-autonomous warm-sensitivity is required to recruit peripheral heat tolerance mechanisms in acclimated animals. Mechanistically, we find a combination of increased sodium leak current and enhanced utilization of the Nav1.3 ion channel to drive their pacemaker-like, warm-sensitive activity. We propose a salient neuronal plasticity mechanism, adaptively driving acclimation to promote heat tolerance.
Gesehen am 28.10.2024
Keywords: Forschungsdaten; Datenbank